THE ANALISYS OF STUDENTS NEED RELATED TO READING AUTHENTIC MATERIALS IN THE SECOND SEMESTER OF UNIVERSITY STUDENTSAT IKIP MATARAM IN ACADEMIC YEAR 2014/2015 - Yuda Januar Pratama (Humanitatis : Journal of Language and Literature, 2018)
This research is aimed to analyze students needs related to reading authentic materials for Second Semester of University Students at IKIP Mataram and to create suitable materials for them based on their needs and their interest. The date of research was collected through giving interview for the lecturer and questionnaire for the students. The data was processed by using frequencies and percentages. In this research SPSS program also was used to process the data. The result of data analysis showed that total means score of all indicators showed that the materials that was developed ‘fairly good’, where the means score of the quality of content was 3.60, the quality of language was 3.00, the quality of supporting video materials was 3.00, the materials was 3.25 and total means score of all indicators was 3.21. The result of reliability was 0.54, and Chronbach’s Alpha was used to get the result.